2D-3C PIV measurement of the near wake of a ducted propeller. (15th May 2022) - Gong, Jie; Ding, Jiang-ming; Wu, Tie-cheng; Jiang, Jia-bing; Guo, Chun-yu
Abstract: The wake dynamics of the ducted propeller is complicated due to the interaction between the nozzle and the propeller. The development of the tip and hub vortices and the contraction of the slipstream in the near wake are analyzed using the time-averaged velocities measured by the towed underwater stereo particle image velocimetry (SPIV) system. The PIV measurement results are in a two-dimensional plane which contains three velocity components (2D-3C), and the representative features of the ducted propeller wake are captured: The decelerated axial velocity area appears near the interface between the accelerated flow and the free stream. The duct accelerates the evolution process of the propeller wake as a faster decrease of the axial velocity in the downstream is observed. The vorticity magnitude the tip vortex structures are smaller than that of the open propeller at the same downstream positions. The wake energy of the ducted propeller diffuses faster owing to the earlier break down of wake vortex structures. Highlights: The decelerated velocity area is captured near the turbulent boundary between the accelerated flow and the free stream. Faster energy transfer from hub vortex to tip vortices for ducted configurations is noted. The radial diffusion of AKE shows the earlier breakdown of the coherent structure of the ducted propeller.